Neutrophil to Lymphocyte Ratio in Early Diabetic Kidney Disease among Patients with Type 2 Diabetes Mellitus - Almalki, Abdullah Hashim; Khobrani, Fatimah Mudaia; Alshamrani, Sarah Mohammed (Archives of Clinical and Biomedical Research, 2020)
Background: Few data are available about the role neutrophil to lymphocyte ratio (NLR) as an inflammatory marker in the early diabetic kidney disease (DKD). Methods: An observational study involving 416 adult patients with type 2 diabetes mellitus (DM) from one center. The study aimed at investigating the relationship between NLR and urine albumin creatinine ratio (uACR) as a marker of early DKD. Results: Among the 416 patients with type 2 DM (Median age 57 [11] years, 40% men and median duration of DM 10 [IQR: 5, 15] years), 169 patients developed albuminuria (Proportion 0.41; 95% CI 0.36, 0.45). The NLR levels were significantly higher among diabetic patients with albuminuria as compared to those without albuminuria; median 1.5 (IQR: 1.1, 2) vs 1.2 (IQR: 1, 1.9), p value 0.004. The receiver operating characteristic analysis of NLR revealed area under the curve of 0.58 (95% confidence interval 0.528 to 0.638; p 0.004). On multivariable analysis; the rate of albuminuria was found higher among patients with HTN (AOR 1.97, 95% CI 1.3 to 2.99; p 0.001); patients with A1c >7 (AOR 2.08, 95% CI 1.21 to 3.59; p 0.008) and patients with NLR score >1.25 (AOR 2.1, 95% CI 1.39 to 3.18; p <0.001). Conclusion: NLR was found to be an independent predictor of albuminuria in patients with type 2 DM.